Effect of Sclerotinia head rot on some bioconstituents of sunflower seed - and K.L. AHUJA, BIPEN KUMAR , S.S. CHAHAL (Indian Phytopathology, 2002)
Healthy and infected sunflower seeds were collected in Ludhiana, Indian Punjab. The biochemical constitution of the seeds was evaluated. Infection by S. sclerotiorum caused a decrease in seed oil, protein, free amino acid, sugar and phenol contentsand an increase in peroxidase and fatty acid content.